BUDAYA ORGANISASI, KOMUNIKASI, DAN MOTIVASI SEBAGAI DETERMINASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT BATAM KOTA - Lestari Putri, Ranisa Eka; Yanti, Sri (Universitas Batam, 2019)
This study aimed to get empirical evidence of the influence of organizational culture, communication, and motivation on employee performance in Batam City District Office. In the stages of testing in this study using the sampling method used is the census. The sample in this study was 43 Employees Head Office Batam City. Methods of data collection conducted by questionnaire.Hypothesis testing is performed using linear regression models and test the T-statistic. Hypothesis testing is done by using SPSS software. Based on the results of testing the first hypothesis, it is known that the organizational culture significantly influence employee performance Batam City District Office. And the results of the second test, it is known that the communication is not significant to the performance of the staff of the Head of Batam. And a third test results, it is known that motivation has a significant influence on employee performance Batam City District Office.